Immunological response to bolus versus multiple injections of hylan G‐F 20 (Synvisc®) in a murine biocompatibility model. Issue 7 (6th February 2014) - Markel, David C.; Jackson, Nancy M.; Esquivel, Amanda O.; Ren, Weiping; Flynn, Jeffrey C.
ABSTRACT Local tissue reactivity to intra‐articular injections of hyaluronic acid hylan G‐F 20 (Synvisc®) has been described. We used a murine biocompatibility model to study the inflammatory response to Synvisc® after a single bolus injection versus the traditional three shot series of injections. Air pouches were established subcutaneously in BALB/c mice, which were injected with phosphate‐buffered saline (PBS), 5 mg ultra‐high molecular weight polyethylene particles (to simulate synthetic joint wear debris, positive control), 0.5 mL Synvisc® (one injection/week for three weeks, harvested 14 days after last injection), or 1.5 mL Synvisc® bolus (harvested either 14 or 28 days after last injection). Inflammatory gene expression and inflammation of air pouch tissue, and serum antibody titers to Synvisc® were determined. Inflammation was observed with all Synvisc® treatments relative to PBS (p < 0.01). However, the three injection series of Synvisc® resulted in significantly (p < 0.05) greater tumor necrosis factor‐alpha gene expression compared to both PBS and bolus single shot Synvisc® harvested after 14 or 28 days. While all Synvisc® treatments resulted in serum antibodies to Synvisc® (p < 0.02 compared to PBS control group), mice that received three injections of Synvisc® had higher levels than mice receiving a single injection (p < 0.01). These results demonstrate that a single bolus injection of Synvisc® led to less inflammation and a lower antibody response when compared to the three‐shot series of injections, supporting the current change in treatment from multiple injections to a single injection of Synvisc®. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1375–1380, 2014.